KAJIAN TEKNO EKONOMI PRODUKSI BAHAN PROPILENA GLIKOL BERBASIS BIOMASSA VIA HIDROGENOLISIS GLISEROL - Galuh Wirama Murti; Arif Darmawan; Nesha Adelia; Nilasari; Dorit Bayu Islam Nuswantoro (Badan Pengkajian dan Penerapan Teknologi, 2020)
Governmental policies that promote biofuels such as biodiesel have led to the generation a largeamounts of glycerol waste as a low-cost raw material. The purpose of this paper is to present a technoeconomic study on the production of biomass-based propylene glycol via glycerol hydrogenolysis,considering hydrogen feeds that partially or fully utilize renewable sources. For analysis andcalculation, computer simulations are carried out using the Aspen Hysys V11 simulator. The technoeconomic analysis is performed by modelling the propylene glycol synthesis process from glycerol,which is then used to calculate the facility capital cost and estimate operating costs to obtain an annualreturn on investment. Sensitivity analysis is also conducted for several parameters on a 36,000ton/year propylene glycol plant. The results showed the production cost was 0.76 USD/kg or 10,802IDR/kg when the hydrogen is generated from the natural gas steam-methane reforming (SMR)process. If the hydrogen is produced from the glycerol steam reforming process, which is fullyrenewable, the plant is not feasible, as indicated by a negative net present value (NPV).